Comparison of Moral and Economic Rights Between Indonesia and France - Eristadora, Stephanie; Habibi, Ahmad; Baehaqi, Faisal; Widyastuti, Tiyas Vika; Mashdurohatun, Anis (Journal of Contemporary Law Studies, 2024)
This article endeavors to conduct a comprehensive legal juxtaposition of moral and economic rights within the contexts of Indonesia and France. Intellectual property rights, specifically copyright, constitute the focal point of analysis, safeguarding various forms of creative expression encompassing literary, artistic, and scientific works. Within the realm of copyright, a fundamental distinction exists between economic rights, which are subject to arbitrary transfer, and moral rights, which inherently vest with the creator or artist and resist divestiture. Employing conceptual and normative approaches, supplemented by data procured from library resources, this research adopts qualitative data analysis techniques, encompassing both traditional and online research methodologies.The findings of this investigation illuminate dissimilarities in the legal frameworks governing intellectual property rights protection between Indonesia and France. France accentuates the significance of cultural and moral rights, prioritizing the intrinsic connection between the creator and their creation. In contrast, Indonesia places greater emphasis on economic considerations and the protection of economic interests. These disparities manifest in the divergent regulatory structures governing industrial design and copyright in each jurisdiction. Notwithstanding these distinctions, the article contends that achieving harmonization and fostering a nuanced understanding of these regulations is imperative to facilitate cross-border collaborations within the global economy and creative industries. Such harmonization is pivotal for advancing the collective interests of nations and creators alike.